Estimating potential silent transfer using baseline viral load measures among people presenting as new to HIV care in Lusaka, Zambia: a cross-sectional study - Michael E Herce; Misinzo Moono; Herbert Kapesa; Jake M Pry; Shilpa Iyer; Theodora Savory; Carolyn Bolton-Moore; Musunge Mulabe; Chilambwe Mwila; Christiana Frimpong (BMJ Open, 2023)
Objectives To estimate potential silent transfer using baseline viral load measures among individuals presenting as new to HIV care in routine HIV clinical settings in Lusaka, Zambia.Design Cross-sectional study.Setting Two large, urban government-operated health facilities supported by the Centre for Infectious Disease Research in Zambia.Participants A total of 248 participants with an incident positive HIV rapid test.Outcome measures The primary outcome measure was HIV viral suppression at baseline (i.e., potential silent transfer), defined as having a viral load ≤1000 RNA copies(c)/mL at the time of initiating HIV care. We also examined viral suppression at ≤60 c/mL.Methods We surveyed and measured baseline HIV viral load as part of the national recent infection testing algorithm among people living with HIV (PLWH) presenting as new to care. Using mixed effects Poisson regression, we identified characteristics among PLWH associated with potential silent transfer.Results Among the 248 PLWH included, 63% were women with median age of 30, and 66 (27% (66/248)) had viral suppression at ≤1000 c/mL and 53 (21% (53/248)) at ≤60 c/mL thresholds, respectively. Participants aged 40+ years had a significantly higher adjusted prevalence of potential silent transfer (adjusted prevalence ratio (aPR): 2.10; 95% CI: 2.08, 2.13) compared with participants aged 18–24 years. Participants reporting no formal education had a significantly higher adjusted prevalence of potential silent transfer (aPR: 1.63; 95% CI: 1.52, 1.75) compared with those completing primary education. Among 57 potential silent transfers who completed a survey, 44 (77%) indicated having tested positive previously at ≥1 of 38 clinics in Zambia.Conclusions The high proportion of PLWH with potential silent transfer points to clinic shopping and/or co-enrolment at multiple care sites simultaneously, suggesting an opportunity to improve care continuity at the time of HIV care entry.